Meningkatkan Keterampilan Dan Hasil Belajar Bahasa Indonesia Tentang Menulis Surat Resmi Melalui Contextual Teaching And Learning (CTL) Pada Siswa Kelas VI SD 6 Getassrabi - Endang Sulistyowati (INOPENDAS: Jurnal Ilmiah Kependidikan, 2019)
The skill of writing official letters and the results of his studies in class VI of SD 6 Getassrabi is very low. It is known that student skills are only 37% with learning completeness only 44%. Based on this, an action is taken to improve it, namely research by applying the Contextual Teaching and Learning (CTL) model. From the implementation of the study it was found that through the application of the CTL model students' skills and learning outcomes increased. Student writing skills become 81%, with completeness of student learning outcomes reaching 88%.